As exportações brasileiras de automóveis para o Mercosul entre 1991 e 2006: criação ou desvio de comercio? - Lemos, Carlos Júlio Santos de (Universidade do Vale do Rio do Sinos, 2009)
The economic growth of countries is based on the growth of world economy, which in turn depends on the development of trade between these countries. The trade integration between countries has been occurring through multilateral negotiations and regional agreements. The theories of international trade show that the increase in international relations promotes economic gains and competitiveness. In the case of Mercosur since 1991 the trade was important for its members and has been intensifying over the years. This study investigates the existence of creation or diversion of trade and start making comparison of the products most relevant in Chapter 87, from 1991 to 2006, including cars, parts and accessories in the Mercosur and its relevance compared to total world exports, as measured by the ROI - Regional “Orientation” Index and RCA – “Revealed” Comparative Advantage, respectively. The results show the existence of three distinct periods for the economy of Mercosur and suggest that those products in the auto
Keywords: Mercosul; orientação regional; automóveis; mercosur; regional orientation; automobiles; Ciências Sociais Aplicadas